Values, Religions and Education in Changing Societies - Jackson, Robert (Dordrecht ;New York Springer Science+Business Media B.V., 2010)
Education is a societal matter and takes place in relation to societal changes. Today, in many countries, it has to grapple with diversity and differences brought about by migration and changes in gender relations. Questions of values, human rights and
Keywords: Social change. Religious education. EDUCATION